Coerência entre princípios e práticas na Wikipédia Lusófona: uma análise semiótica - Paulo Henrique Souto Maior Serrano (2011)
This paper presents the method, the analysis and the results of a study that examined the operation dynamics and consistency between the guidelines of conduct and practice of editing at the Lusophone version of Wikipedia, the free encyclopedia. This work uses information and contentpublished under the Creative Commons / Share alike 3.0 that indicates the need to distribute the resulting work under the same license. The online encyclopedia can be freely changed by users that browse its contents. Discussions on the permanence or alteration of information published are held in a special discussion page where people can argue about the differences of opinion and reach consensus. This process occurs from cognitive and pragmatic sanctions given to themes and figures that make up the thematic isotopy of users enunciation. The identification of these elements in this dissertation, was carried out by Greimas' semiotics. Sanctions should pragmatically represent theguidelines of the collaborative process on Wikipedia, but there are institutionalized rules that are presented to users as the five pillars of Wikipedia. The five pillars are about the encyclopedism, neutral point of view, free license, community conviviality and liberality in the rules. The statute assigns values to the practice of encyclopedias and information that are published by them. These values were defined by tensive semiotics and compared with the cognitive and pragmatic sanctionsof the isotopies enunciated by users, to check the consistency between what is being requested by Wikipedia and what is being done by their contributors. The results of this comparison show some similarities and differences between discourse and practice, indicating ownership of Wikipedia by its users and the need for more accuracy and criteria in conflicting issues or controversies for the permanence of information on the page entry. The verifiability of the information was presented asa greatly appreciated theme by users, indicating the importance of the veracity of reference sources and the verification of information. The freedoms and distribution of powers introduced by the principles are denied on the practice of editing. Wikipedia presented itself as a very liberal and tolerant encyclopedia, giving substance to the collaboration, but, in practice, very restrictive and careful when it comes to the permanence of a content in the article page.